Automated evaluation of website navigability: an empirical validation of multilevel quality models. Issue 8 (13th August 2012) - Vaucher, Stéphane; Moulart, Antoine; Sahraoui, Houari; Habra, Naji; Kienle, Holger; Di Lucca, Giuseppe; Kontogiannis, Kostas
ABSTRACT Websites are an important and efficient means of communication for companies wishing to interact with their clients. Therefore, research has focused on evaluating how websites should be structured to ensure their quality. The majority of this research has focused on evaluating the quality of individual pages or that of a site as a whole. In this article, we propose the use of two‐level models that combine evaluations at the page level with evaluations at the site level, and applied them to the problem of evaluating the navigability of websites. To test our models, we conducted a study with 21 subjects who had to complete navigation tasks on several websites, and compared their quality judgments to those produced by single and two‐level quality models. We found that two‐level models are better predictors of navigability. Finally, we show how two‐level models are able to suggest modifications to improve site navigability. Copyright © 2012 John Wiley & Sons, Ltd.